Strategy, power and CSR : practices and challenges in organizational management - Atristain-Suárez, Connie; García-Álvarez, Santiago (Emerald Publishing Limited, 2020)
Organizational management, along with strategy, is the most important part of business administration. Directors must know how to manage people, make decisions and, above all, have the ability to create strategies that help organizations achieve their objectives, greater strategic competitiveness, and above-average returns. In today's global and complex environment, traditional views towards organizational management are not enough for businesses to thrive. It's only by bringing together different approaches can management styles develop fast enough to keep pace with the ever-changing big picture. In this innovative new look at organizational management, expert authors Santiago García-Álvarez and Connie Atristain-Suárez explore how looking through lenses of philosophy, health, communication, law, engineering, pedagogy and policy can affect a modern organization's prospects. Built through the collective and collaborative work of the research professors at the Universidad Panamericana, this work includes interdisciplinary approaches to real-world problems. For students and researchers of business and management, this is an unmissable read.